Advanced English for Mathematicians - Olena Gorenko; Горенко Олена; Horenko Olena (Transcarpathian Hungarian College-“RIK-U” LLC, 2020)
Abstract. Our age is the age of communication. In the atmosphere of constantly developing scientific technologies we have to resort to various kinds of communication to tackle appropriate subjects. For the future specialists in the sphere of mathematics and informatics such a kind of communication includes the following abilities: to comprehend special literature and express oneself on different professional topics. On the one hand, such an approach helps the students to enlarge vocabulary of special terminology within the frames of those grammar constructions (infinitival, gerundial and participial), which are widely used in the language of science. On the other hand, it helps to develop practical skills in oral English for professional purposes, to learn the models for writing annotations to scientific texts.

Резюме. Характерною ознакою сучасної доби є суттєва інтенсифікація комунікативної взаємодії. У той час, коли постійно розвиваються, вдосконалюються та поглиблюються різноманітні наукові досягнення і технології, фахівці повинні вміти спілкуватися англійською мовою у професійній сфері. Цей навчальний посібник призначений для студентів – математиків та інформатиків. Його структуру складають оригінальні спеціальні тексти, граматичні, лексичні, лексико-граматичні вправи та комунікативні завдання. З одного боку, такий підхід розширює мовну компетенцію студентів, а з іншого – дозволяє вийти на відповідний рівень як усного, так і письмового фахового спілкування.
Англійська мова для математиків
https://kmf.uz.ua/wp-content/uploads/2020/11/olena-horenko_adv-eng-for-math_13-11-2020.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008460
Keywords: English language; mathematicians; informatics